Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am trying to solve $z^6 = 1$ where $z\in\mathbb{C}$. So What I have so far is : $$z^6 = 1 \rightarrow r^6\operatorname{cis}(6\theta) = 1\operatorname{cis}(0 + \pi k)$$ $$r = 1,\ \theta = \frac{\pi k}{6}$$ $$k=0: z=\operatorname{cis}(0)=1$$ $$k=1: z=\operatorname{cis}\left(\frac{\pi}{6}\right)=\frac{\sqrt{3} + i}{2}$$ $$k=2: z=\operatorname{cis}\left(\frac{\pi}{3}\right)=\frac{1 + \sqrt{3}i}{2}$$ $$k=3: z=\operatorname{cis}\left(\frac{\pi}{2}\right)=i$$ According to my book I have a mistake since non of the roots starts with $\frac{\sqrt{3}}{2}$, also even if I continue to $k=6$ I get different (new) results, but I thought that there should be (by the fundamental theorem) only 6 roots. Can anyone please tell me where my mistake is? Thanks!

share|improve this question
    
So what is written in your book? –  draks ... Feb 6 '12 at 13:46
    
$cis=cos+i\cdot sin$? –  Rasmus Feb 6 '12 at 14:01
    
yes its is. why do i have to write 12 chars? –  yotamoo Feb 6 '12 at 14:10
    
You want $\theta=\frac{2\pi k}6 = \frac{\pi k}3$. –  Thomas Andrews Feb 6 '12 at 14:12
    
What ever "start with ...", I think there is a 2 missing. Shouldn't it be ${\rm cis}(x)=e^{ix}=e^{i(x+2k\pi)}$? This would also drop the solution that "starts with $\sqrt{3}/2$", which is a root of -1 anyhow. –  draks ... Feb 6 '12 at 14:15

4 Answers 4

You have to write your equation into the form

$$z^6=e^{2in\pi}=1$$

then

$$z=e^{in\frac{\pi}{3}}$$

and from this you can read off all the solutions.

share|improve this answer
1  
But isn't that what he did? ${\rm cis} (x) = e^{ix}$ –  draks ... Feb 6 '12 at 13:48
    
@draks: You are right. Sorry for the repetition. –  Jon Feb 6 '12 at 13:53
    
That's because you divided wrong, @Jon. $\frac{2\pi n i}6 \neq \frac{\pi n i}6$ –  Thomas Andrews Feb 6 '12 at 14:14
    
@ThomasAndrews: Thank you a lot! I will fix this embarrassing mistake. –  Jon Feb 6 '12 at 14:18

It may be of interest to point out that this can also be solved using basic high school algebra factorization methods (i.e. no trig is needed). Begin by factoring as a difference of squares. Then factor the sum and difference of cubes that arise. Finally, put each of the resulting factors equal to $0$ and solve.

$$x^6 - 1 \; = \; (x^3 - 1)(x^3 + 1) \; = \; (x-1)(x^2 + x + 1)(x+1)(x^2 - x + 1)$$

Now solve the following equations. Use the quadratic formula for two of them.

$$x - 1 = 0$$

$$x^2 + x + 1 = 0$$

$$x+1=0$$

$$x^2 - x + 1 = 0$$

share|improve this answer

You need $2\pi$ where you had $\pi$. Thus for $k=1$ you should get $$ \cos\left(\frac{2\pi\cdot1}{6}\right) + i \sin\left(\frac{2\pi\cdot1}{6}\right). $$

share|improve this answer

I will solve $z^6=1$ where $z∈\mathbb{C}$. First I will take off all data: $r=1$, $\theta = 0$, $n=6$ and $k=0,1,2,3,4,5$ then

For $k=0: w_1=\sqrt[6]{1}[\cos{\frac{2\pi (0)}{6}}+ i\sin{\frac{2\pi (0)}{6}}]=1[\cos{0}+i \sin{0}]$ therefore $z_1=\cos{0}+i\sin{0}$ finally $z_1=1$

For $k=1: w_2=\sqrt[6]{1}[\cos{\frac{2\pi (1)}{6}}+ i\sin{\frac{2\pi (1)}{6}}]=1[\cos{\frac{\pi}{3}}+i \sin{\frac{\pi}{3}}]$ therefore $z_2=\cos{\frac{\pi}{3}}+i\sin{\frac{\pi}{3}}$ finally $z_2=\frac{1}{2}+\frac{\sqrt{3}}{2}i$

For $k=2: w_3=\sqrt[6]{1}[\cos{\frac{2\pi (2)}{6}}+ i\sin{\frac{2\pi (2)}{6}}]=1[\cos{\frac{2\pi}{3}}+i \sin{\frac{2\pi}{3}}]$ therefore $z_3=\cos{\frac{2\pi}{3}}+i\sin{\frac{2\pi}{3}}$ finally $z_3=-\frac{1}{2}+\frac{\sqrt{3}}{2}i$

For $k=3: w_4=\sqrt[6]{1}[\cos{\frac{2\pi (3)}{6}}+ i\sin{\frac{2\pi (3)}{6}}]=1[\cos{\pi}+i \sin{\pi}]$ therefore $z_4=\cos{\pi}+i\sin{\pi}$ finally $z_4=-1$

For $k=4: w_5=\sqrt[6]{1}[\cos{\frac{2\pi (4)}{6}}+ i\sin{\frac{2\pi (4)}{6}}]=1[\cos{\frac{4\pi}{3}}+i \sin{\frac{4\pi}{3}}]$ therefore $z_5=\cos{\frac{4\pi}{3}}+i\sin{\frac{4\pi}{3}}$ finally $z_5=-\frac{1}{2}-\frac{\sqrt{3}}{2}i$

For $k=5: w_6=\sqrt[6]{1}[\cos{\frac{2\pi (5)}{6}}+ i\sin{\frac{2\pi (5)}{6}}]=1[\cos{\frac{5\pi}{3}}+i \sin{\frac{5\pi}{3}}]$ therefore $z_6=\cos{\frac{5\pi}{3}}+i\sin{\frac{5\pi}{3}}$ finally $z_6=\frac{1}{2}-\frac{\sqrt{3}}{2}i$

I hope this help you!!!

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.